Osteogenic differentiation factors of multipotent mesenchymal stromal cells in the current understanding; Current Pharmaceutical Design; Vol. 27, iss. 35 - Yurova K. A.; Melashchenko E. S.; Khaziakhmatova O. G.; Melashchenko V. V.; Shunkin E. O. Egor; Norkin I. K. Igor; Ivanov P. A. Pavel; Khlusov I. A. Igor Albertovich; Litvinova L. S. (2021, 2021)
Title screen